1997
DOI: 10.1152/ajpregu.1997.273.1.r293
|View full text |Cite
|
Sign up to set email alerts
|

Renal oxygenases: differential contribution to vasoconstriction induced by ET-1 and ANG II

Abstract: In the rat isolated perfused kidney, 5,8,11,14-eicosatetraynoic acid, an inhibitor of all pathways of arachidonic acid (AA) metabolism, diminished endothelin-1 (ET-1)- and angiotensin II (ANG II)-induced renal vasoconstriction by approximately 60-70%. We then examined the individual contribution of each oxygenase, cyclooxygenase (COX), lipoxygenase (LOX), and cytochrome P-450 (CYP) to the vasoconstrictor effects of ET-1 and ANG II. Inhibition of COX with indomethacin reduced by 30-40% the vasoconstrictor respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
79
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(88 citation statements)
references
References 0 publications
8
79
0
1
Order By: Relevance
“…For example, ANG II and endothelin stimulate the renal formation of 20-HETE, which contributes to the renal vasoconstrictor and natriuretic actions of these hormones (11,12,35). The expression of CYP4A enzymes and the formation of 20-HETE are also elevated in the kidney of ANG II-infused hypertensive rats (1), and 20-HETE contributes to the development of hypertension and end-organ damage in this model (1,27,28).…”
Section: Discussionmentioning
confidence: 99%
“…For example, ANG II and endothelin stimulate the renal formation of 20-HETE, which contributes to the renal vasoconstrictor and natriuretic actions of these hormones (11,12,35). The expression of CYP4A enzymes and the formation of 20-HETE are also elevated in the kidney of ANG II-infused hypertensive rats (1), and 20-HETE contributes to the development of hypertension and end-organ damage in this model (1,27,28).…”
Section: Discussionmentioning
confidence: 99%
“…7,9,10,16, 22 Oyekan et al, using in vitro and in vivo techniques, have shown that the CYP450 hydroxylase pathway contributes to the ET-1-evoked decrease in renal blood flow, but the role of the COX pathway appears to be complex. 7,16,23 In the isolated perfused kidney, COX inhibition attenuated the renal vasoconstrictor response to ET-1, 16 but when studied in vivo, the COX inhibitor indomethacin potentiated the decrease in glomerular filtration rate elicited by ET-1. 7 These paradoxical findings demonstrating COX metabolites as positive and negative contributors to the ET-1-mediated vasoconstriction are not limited to the renal vasculature and may reflect experimental conditions or species variation.…”
Section: Discussionmentioning
confidence: 99%
“…In the isolated perfused kidney, ET-1 increases the release of 20-HETE into the renal effluent. 16 ET-1 also has the capacity to increase production of vasodilatory prostaglandins (PGs), PGI 2 and PGE 2 , as well as vasoconstrictor COX metabolites, PGF 2␣a , PGH 2 , and TX. 1,10,14,21 Interestingly, the CYP450 hydroxylase metabolite 20-HETE can be transformed by COX to a vasoconstrictor PGH 2 analogue, 20-OH PGH 2 .…”
Section: Discussionmentioning
confidence: 99%
“…20-HETE also increases Ca 2ϩ influx via L-type Ca 2ϩ channels in the cerebral vasculature (16) and plays a critical role in the mechanism underlying the autoregulation of cerebral blood flow in the rat (2,15,18). Vasoconstrictor peptides like angiotensin II and ET stimulate the formation of 20-HETE in VSM, and 20-HETE potentiates the vasoconstrictor response to these agents (11,31). Nitric oxide (NO) inhibits the formation of 20-HETE in VSM, and this contributes to the vasodilator actions of NO in the cerebral circulation (2,37).…”
mentioning
confidence: 99%